Solitary City: Time, Space and Urban Policy - Oshiro, Jun (The Manchester school, 2017)
We examine the positive and normative implications of externality‐generating activities in the setting of an urban economy wherein households equilibrate their time allocation between social networking and business networking. Since every interaction is time consuming, households face a trade‐off between enjoying social interaction and participating in business networks. We develop a monocentric city model with a time allocation decision to investigate the influence of externality‐generating activities on the spatial structure of cities and assess the urban policies meant to facilitate social interaction. Two interdependent magnification forces are generated from social interactions and human capital spillovers. Households are subject to too much social isolation when a positive correlation exists between agglomeration and productivity.